Strategi Pemasaran dan Program Pemasaran Global di Pasar Indonesia - Rifaldi Dwi Syahputra; Putri Khairani Pratiwi; Rizka Azriani Tanjung; Suhairi Suhairi (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2024)
Globalization is a new challenge for companies in the implementation of marketing strategy. Due to globalization, companies are required to compete with world class companies that have large capital and higher quality products. Indonesia currently becomes the market target for global companies to enjoy huge profits, while the Indonesian companies lost the competition. This study aims to obtain global marketing strategy for Indonesian companies in Indonesian market. Research method used is descriptive analisys. Merger between adaptation of marketing strategies and standard marketing strategy is appropriate strategy in Indonesian market.